GENETIC POLYMORPHISMS AS THE RISK FACTOR IN THE DEVELOPMENT OF OSTEOARTHRITIS - S. B. Panina (Медицинский вестник Юга России, 2014)
It’s well-known that osteoarthritis (OA) is a widespread form of degenerative joint disorder that has the significant genetic component. The studies concerning the role of various candidate genes in the OA development are analyzed; much attention is given to the exploration of matrix metalloproteinases, their inhibitors and interleukin genes polymorphisms. The paper describes the results of up-to-date genome-wide association scanning and meta-analyses of polymorphisms associated with osteoarthritis in detail. The paper also considers the problem of the linkage between epigenetic alterations and the susceptibility to OA.